2015
DOI: 10.4315/0362-028x.jfp-14-199
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Survey of Locally Grown Lettuce Sold at Farmers' Markets in Vancouver, British Columbia

Abstract: Increased consumer demand for fresh leafy produce has been paralleled by an increase in outbreaks and illness associated with these foods. Presently, data on the microbiological quality and safety of produce harvested in the Lower Mainland of British Columbia is lacking. Therefore, fresh green, red, and romaine lettuce samples (n = 68) were obtained from five regional farmers' markets in late summer of 2012 and subsequently analyzed to determine total numbers of aerobic bacteria, coliforms, and Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…The AMB levels in 5 kinds of fresh vegetables (FV) taken immediately from soil were within the range of 3.54-6.32 log 10 CFU g -1 , for isolates recovered at 30 o C. The AMB levels in the same kinds of vegetables sold at retail in the markets (VR), described often in the literature as unprocessed vegetables (UV) [4], were significantly lower, ranging from 0.00-5.55 log 10 CFU g -1 . The levels of AMB noted in the presented study for FV and VR were similar to those reported by Nguz et al [6] (Zambia), Aycicek et al [1] (Turkey), Oliveira et al [7] and Soriano et al [25] (Spain), Seow et al [8] (Singapore), Cardamone et al [4] (Italy), Johnston et al [26,27] (USA), Ryu et al [3] (Korea), and by Wood et al [28] (Canada), but lower compared to data reported by Abadias et al [2] and Ercolani [29] (Spain), De Giusti et al [11] (Italy), Viswanathan and Kaur [5] (India), and by Hagenmaier and Baker [30], Valentin-Ban et al [31] and Korir et al [32] (USA).…”
Section: Discussionsupporting
confidence: 90%
“…The AMB levels in 5 kinds of fresh vegetables (FV) taken immediately from soil were within the range of 3.54-6.32 log 10 CFU g -1 , for isolates recovered at 30 o C. The AMB levels in the same kinds of vegetables sold at retail in the markets (VR), described often in the literature as unprocessed vegetables (UV) [4], were significantly lower, ranging from 0.00-5.55 log 10 CFU g -1 . The levels of AMB noted in the presented study for FV and VR were similar to those reported by Nguz et al [6] (Zambia), Aycicek et al [1] (Turkey), Oliveira et al [7] and Soriano et al [25] (Spain), Seow et al [8] (Singapore), Cardamone et al [4] (Italy), Johnston et al [26,27] (USA), Ryu et al [3] (Korea), and by Wood et al [28] (Canada), but lower compared to data reported by Abadias et al [2] and Ercolani [29] (Spain), De Giusti et al [11] (Italy), Viswanathan and Kaur [5] (India), and by Hagenmaier and Baker [30], Valentin-Ban et al [31] and Korir et al [32] (USA).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, a lower resistance was recorded to gentamicin (22%), which is in line with various studies [10,39], highlighting the promising treatment of E. coli by gentamicin as demonstrated by Fadlallah et al [40].…”
Section: Resistance To Antimicrobialssupporting
confidence: 87%
“…The four samples of mizuna, the only leafy green tested, were grown in different Lada root modules at different times and counts ranged from 3.1 × 10 3 -8.7 × 10 5 . When compared to field grown or market produce of similar types these numbers are well within the expected range of microbial densities or even lower (Holvoet et al, 2015;Wood et al, 2015;Fröhling et al, 2018;Hummerick et al, unpublished data).…”
Section: Introductionsupporting
confidence: 61%
“…Bacterial and fungal counts on fresh plant material are not necessarily an indication of the food quality and microbiological safety of the item and vary depending on the type of plant (Leff and Fierer, 2013;Qadri et al, 2015). Studies show that leafy greens grown in the field or greenhouse have a range of approximately 4-8 log 10 CFU bacterial counts per gram of sample while yeast and mold counts on lettuce are reported in the range of 2-5 log 10 (Valentin-Bon and Jacobson, 2008;Rastogi et al, 2012;Jackson et al, 2013;Holvoet et al, 2015;Wood et al, 2015;Hagenmair and Baker, 2016;Oyinlola et al, 2017;Fröhling et al, 2018;Zhang et al, 2018). The microbial counts on lettuce leaves grown on ISS in VEG-01A, B and both harvests from VEG-03A were relatively low on average when compared to farm or market produce counts of similar type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation